Intensity of Caring About an Action’s Side-Effect Mediates Attributions of Actor’s Intentions - Liao, Yu; Sun, Yujia; Li, Hong; Deák, Gedeon O.; Feng, Wenfeng (Frontiers in Psychology, 2018)
The side-effect effect (SEE) is the observation that people's intuition about whether an action was intentional depends on whether the outcome is good or bad. The asymmetric response, however, do not represent all subject's judgments (Nichols & Ulatowski, 2007). It remains unexplored on subjective factors that can mediate the size of the asymmetric response characterized in SEE. Thus, the current study investigated whether an individual related factor, specifically, whether adults' intensity of caring about an outcome of someone's actions influences their judgments about whether that person intended the outcome. We hypothesized that participants' judgments about fictional agents' responsibility for their action's side-effects would depend on how much they care about the domain of the side-effect. In two experiments, intensity of caring affected participants' ascription of intention to an agent’s negative unintended side-effect. The stronger ascription of intentionality to negative than positive side-effects (i.e., the Side-Effect Effect; Knobe, 2003) was found only in domains in which participants reported higher levels of caring. Also, intensity of caring increased intentionality attributions reliably for negative side-effects but not for positive side-effects. These results suggest that caring about a domain mediates an asymmetrical ascription of intentionality to negative more than positive side-effects.